2007
DOI: 10.3174/ajnr.a0846
|View full text |Cite
|
Sign up to set email alerts
|

Language Dysfunction After Stroke and Damage to White Matter Tracts Evaluated Using Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:Knowledge of the anatomic basis of aphasia after stroke has both theoretic and clinical implications by informing models of cortical connectivity and providing data for diagnosis and prognosis. In this study we use diffusion tensor imaging to address the relationship between damage to specific white matter tracts and linguistic deficits after left hemisphere stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 33 publications
12
127
0
2
Order By: Relevance
“…14,15 Regarding language function, early reports established association of lesions in specific cortical anatomic locations in the left frontal lobe with clinically recognized symptoms, defined as aphasia. 16 With time, subcortical pathways, such as the SLF, particularly its subdivision, the AF, [17][18][19] were also shown to be involved in language function. 20 Identification of language tracts by DTI has been pursued for a long time, and the imaging technique gained high acceptance in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Regarding language function, early reports established association of lesions in specific cortical anatomic locations in the left frontal lobe with clinically recognized symptoms, defined as aphasia. 16 With time, subcortical pathways, such as the SLF, particularly its subdivision, the AF, [17][18][19] were also shown to be involved in language function. 20 Identification of language tracts by DTI has been pursued for a long time, and the imaging technique gained high acceptance in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using DTI techniques and various types of tractography in patients with acquired brain damage have shown that tracts, such as the arcuate fasciculus (AF), contribute to distinct language production behaviors (Ivanova et al, 2016), particularly mapping sounds with articulatory (motor) stereotypes (Breier, Hasan, Zhang, Men, & Papanicolaou, 2008;Kümmerer et al, 2013), and the processing of complex syntax (Grossman et al, 2013;Wilson et al, 2011). Temporal tracts, such as the inferior longitudinal fasciculus (ILF), inferior frontal-occipital fasciculus (IFOF), and potentially also the uncinate fasciculus (UF) and middle longitudinal fasciculus, have been shown to be mainly involved in language comprehension (Ivanova et al, 2016;Kümmerer et al, 2013).…”
Section: Diffusion Mrimentioning
confidence: 99%
“…Classic clinical-anatomic correlations 2,25 were met pertaining stroke topography in relation to the aphasic syndrome presented in almost 95% of studied subjects. The two patients who did not correspond to the expected brain lesion site could have some individual variation in the cytoarchitecture of language networks and, with specific regard to the patient with Wernicke's aphasia, the language disturbance could be attributed to a temporary hypoperfusion of the left temporal cortex in the acute phase, or to a case of crossed aphasia with predominant impairment in comprehension due to dysfunctional neural tissue surrounding the original lesion.…”
Section: Resultsmentioning
confidence: 99%
“…[1] A brief history of the acute symptoms had to be reported by the patient (whenever possible) or a relative, including data on cardiovascular risk factors and socialeducational information, along with a complete neurological exam and a succinct assessment for hearing impairment (listening to finger-scratching with closed eyes, in each ear at once) and visual acuity; [2] Patients were then tested for attentional deficits by means of the "A" Random Letter Test 7 , being required to tap the unimpaired hand on the desk immediately after hearing the letter "A" (75 letters were orally presented by the examiner, 20 of them were "A" letters); [3] Handedness was assessed according to a fivepoint scale of the Edinburgh Inventory 8 for performance in writing, tooth-brushing, catching food with a spoon, opening a box, drawing, using a knife without fork, sweeping the floor (upper hand on the broomstick), throwing a ball, holding scissors, and striking a match; [4] Visual perception was tested by showing the patients ten abstract figures in several levels of difficulty, each of them displayed for ten seconds, soon after which they would have to point to it among four other figures (scored as hit-or-miss) 9 ;…”
Section: Methodsmentioning
confidence: 99%